THE USE OF AUTHENTIC MATERIALS IN TEACHING READING COMPREHENSION OF SHORT FUNCTIONAL TEXTS - Wilarsih, Yuyun; Marbun, Rismaya; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe objective of this research was to find out whether there was any improvement on students’ reading comprehension of short functional text after being taught using authentic text materials. Therefore the method used in this research was classroom action research. This research was conducted in two cycles. Cycle 1 consisted of three meetings and cycle 2 consisted of two meetings. The subject of this research was 22 students of eight grade students of SMP Tunas Karya Pontianak in academic year 2015/2016. The researcher used observation and students’ achievement test to collect the data. The researcher elaborated the result of observation and students’ achievement test result in order to get the research findings. The results of this research showed that there was any improvement on students’ reading comprehension after being taught using authentic materials. After the actions were implemented, the students showed some improvements. They could focus on the lesson and actively participated in teaching learning process. They showed their enthusiastic in reading the text. They also could find the detail information from the text and increased their vocabulary mastery. The students’ individual score in comprehending short functional text also improved and the result was satisfying. In conclusion, the use of authentic materials improved the students’ reading comprehension of short functional texts. Keywords: Authentic mateials, reading comprehension, short functional texts